Alternatif Pengelolaan Keuangan Haji di Indonesia - Septiana, Nurul Izzati (Universitas Islam Raden Rahmat, 2017)
This research aims to construct the alternative of hajj fund management in Indonesian Islamic Bank. This research uses qualitative method and use descriptive analysis method to analyze the data. From the result of this research are found the alternative concept of hajj fund management in Islamic bank using musyarakah muatanaqishah contrac which is placed in the first parties fund in Islamic bank.